1972
DOI: 10.1136/hrt.34.3.252
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a beta-adrenergic receptor blocker in myocardial infarction treated for one year from onset.

Abstract: In a double-blind trial alprenolol IOO mg four times daily or placebo was given to 87 patientsfor one year from onset of their acute myocardial infarction. Patients were assessed on five occasions after their discharge from hospital. The mortality and hospital readmission rates were not significantly different in the two groups. This also applied to the incidence of cardiac failure, exertional dyspnoea, andfrequency of ventricular ectopic beats. The incidence of angina pectoris and the consumption of trinitrin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
1

Year Published

1976
1976
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(17 citation statements)
references
References 9 publications
0
16
1
Order By: Relevance
“…The conclusions of this study, therefore, do not support the conclusions of the study by Ahlmark et al (1974) in which a reduction of re-infarction as well as sudden death is claimed. It is not immediately obvious why these results are in conflict with those previously reported by Reynolds and Whitlock (1972) but a possible explanation is that the latter study involved too few patients and was of insufficient duration to show a difference. Furthermore, that study was not designed solely to examine the effects of ,-antagonists on morbidity and mortality.…”
Section: Secondary Prevention Studiescontrasting
confidence: 84%
See 1 more Smart Citation
“…The conclusions of this study, therefore, do not support the conclusions of the study by Ahlmark et al (1974) in which a reduction of re-infarction as well as sudden death is claimed. It is not immediately obvious why these results are in conflict with those previously reported by Reynolds and Whitlock (1972) but a possible explanation is that the latter study involved too few patients and was of insufficient duration to show a difference. Furthermore, that study was not designed solely to examine the effects of ,-antagonists on morbidity and mortality.…”
Section: Secondary Prevention Studiescontrasting
confidence: 84%
“…Reynolds and Whitlock (1972) have reported on their experience of a double-blind prospective study in which the n-antagonist alprenolol was administered in a dose of 100 mg four times daily or a placebo to a total of eighty-seven patients from the time of admission to the coronary care unit until 12 months had elapsed. Treatment was administered in random order and any patient who subsequently was shown not to have an acute myoacrdial infarction was withdrawn from the study.…”
Section: Secondary Prevention Studiesmentioning
confidence: 99%
“…Neither the study by Baber et al (1980) including 720 patients, nor the study by including 388 patients could show any reduction in mortality related to propranolol or atenolol treatment after myocardial infarction. Reynolds and Whitlock (1972) found no difference in mortality between alprenolol-and placebo-treated patients. Two years later Ahlmark et al (1974) reported from an open study that alprenolol treatment was associated with a reduction in mortality.…”
Section: Beta Adrenergic Blockadementioning
confidence: 74%
“…Some of the trials have dealt with too few patients, having had too few endpoints, to produce any mean ingful results (9,14,15). Several studies did not deal with a representative group of patients since the placebo mortality rate was much lower than expected in a nonselected group of patients or the drop-out rates were high (9,11,12,13). In the study by Barber et al (10) a high oral dose was administered as soon as possible after onset of symptoms.…”
Section: Nonconclusive Trialsmentioning
confidence: 99%